745 INTERDISCIPLINARY EVALUATION IN RESISTANT ARTERIAL HYPERTENSION. (15th December 2022) - Galli, Verdiana; Trento, Laura; Galuppi, Enrico; Casal, Matteo; Cecchin, Eleonora; Fezzi, Simone; Castaldi, Gianluca; Widmann, Maddalena; Ruzzarin, Alessandro; Marin, Federico; Gambaro, Alessia; Pesarini, Gabriele; et al.
Abstract: Background: Arterial hypertension is a complex and in most cases multifactorial pathology. Despite the numerous pharmacological treatments available, it is estimated that in Europe only 25%-39% of hypertensive patients achieve adequate blood pressure (BP) control. Renal arteries denervation (RDN) is an additional therapeutic weapon, complementary to Optimal Medical Therapy (OMT) in patients with resistant or refractory primary (or essential) arterial hypertension. In order to improve patients management and select those who are eligible for renal denervation, our Center has established the Interdisciplinary Group for the Treatment of Resistant Arterial Hypertension (G.I.T.I.A.R.), including Cardiologists, Nephrologists, Internists and Geriatricians. Methods: From January 2018 to July 2022 the G.I.T.I.A.R. held twelve meetings evaluating 62 patients with resistant or refractory forms of arterial hypertension, contraindications or intolerance to antihypertensive drugs, suspected secondary or pseudoresistant forms (i.e. linked to poor patient compliance, drugs and/or inadequate dosages, concomitant intake of substances with hypertensive effect, incorrect measurements). For each of them, medical therapy was optimized and the need for second level diagnostic tests, multi-specialist follow-up and RDN candidacy were assessed. After three, six, twelve months and then annually following RDN, the patients underwent clinical and multi-specialist evaluation (where deemed appropriate), blood tests monitoring and 24-hour ambulatory blood pressure monitoring (ABPM). Results: Of the 62 patients evaluated by the G.I.T.I.A.R., 64.5% (n=40) were male. The mean age at the time of evaluation was 64 years (range 18-87). After the first collegial discussion, 46.8% (n=29) have been declared eligible for RDN, while 53.2% (n=33) of the patients was initially rejected: 39.4% of these (n=13) for suspected or ascertained secondary hypertension, 12.1% (n=4) for the possibility of further optimization of medical therapy, 48.5% (n=16) for the presence of inclusion or exclusion criteria of ongoing studies design. Among the excluded patients, six presented moderate renal artery stenosis on non-invasive imaging: in two patients (33.3%) the stenosis turned out to be hemodynamically significant on angiographic and functional evaluation (Pd/Pa measurement), so renal angioplasty was performed; RDN was performed in the remaining 66.7% (n=4), in which a hemodynamic significance of the stenosis was excluded. Of the subgroup who had optimized medical therapy, one patient (25%) was subsequently referred to RDN for failure of all pharmacological strategies, while 3 of 4 (75%) achieved adequate BP control. Conclusions: Resistant arterial hypertension is associated with an increased risk of development and progression of cardiovascular and renal diseases, with a significant impact on mortality and morbidity. Renal denervation has proved to be an effective and safe therapeutic strategy, complementary to OMT, whose selection of the ideal patient actually represents one of the greatest challenges. The integrated multidisciplinary approach improves the management of the hypertensive patient, the individualization of therapy and allows the identification of subjects who may benefit from RDN.